Prevalence of screen addiction and its association with screen use behavior and type of content consumed in the general population of Mumbai metropolitan region - Rao, Shirish; Gupta, Vidushi; Ambike, Amey; Adarkar, Shilpa; Mhatre, Pauras; Saraf, Prashant; Raul, Shreeya; Paranjape, Raghav; Dedhia, Keval; Inamdar, Gayatri; Chavan, Pavan; Shinde, Purva; et al. (International Journal Of Community Medicine And Public Health, 2023)
Background: Varied prevalence of internet, gaming and smartphone addiction have been estimated across different regions. Though gaming and internet addiction have already been recognized, the emerging trend of binge-watching also demands attention. There was a need to estimate their prevalence using a uniform scale, compare addiction scores and also assess its association with content consumed and screen use behavior. Methods: A cross-sectional study was conducted among 252 participants who were recruited using stratified random sampling and were interviewed using digital addiction scale and a self-designed questionnaire (CVR>0.65). Results: The prevalence of screen addiction was found to be 13% and found to be associated with age (p<0.01), sex (p<0.01), type of content consumed (p<0.05), device used (p<0.01), self-reported causes (p<0.01), withdrawal (p<0.01) and screen use specific psychological phenomenon (p<0.01). Addiction scores of gamers, social media users and binge watchers were comparable (p>0.05). Conclusions: The prevalence of screen addiction is substantially high, particularly in the younger population. This study also highlights the strong association of screen use behavior and type of content consumed and apps used with addictive screen use. The similarity in addiction scores and associated factors also support the use of umbrella term ‘Screen Addiction’ to group all kinds of addictive screen usage.